The Small RNA DsrA Influences the Acid Tolerance Response and Virulence of Salmonella enterica Serovar Typhimurium - Ryan, Daniel; Ojha, Urmesh K.; Jaiswal, Sangeeta; Padhi, Chandrashekhar; Suar, Mrutyunjay (Frontiers in Microbiology, 2016)
The Gram-negative, enteropathogen Salmonella enterica serovar Typhimurium (S. Typhimurium) is exposed to various stress conditions during pathogenesis, of which acid stress serves as a major defence mechanism in the host. Such environments are encountered in the stomach and Salmonella containing vacuole of phagocytic and non-phagocytic cells. It is only recently that small RNAs (sRNAs) have come to the forefront as major regulators of stress response networks. Consequently, the sRNA DsrA which regulates acid resistance in Escherichia coli, has not been characterized in the acid tolerance response (ATR) of Salmonella. In this study, we show dsrA to be induced 2 and 3 fold under adaptation and challenge phases of the ATR respectively. Additionally, an isogenic mutant lacking dsrA (ΔDsrA) displayed lower viability under the ATR along with reduced motility, feeble adhesion and defective invasion efficacy in-vitro. Expression analysis revealed down regulation of several Salmonella pathogenicity island-1 (SPI-1) effectors in ΔDsrA compared to the wild-type, under SPI-1 inducing conditions. Additionally, our in-vivo data revealed ΔDsrA to be unable to cause gut inflammation in C57BL/6 mice at 72 hours post infection, although intracellular survival and systemic dissemination remained unaffected. A possible explanation may be the significantly reduced expression of flagellin structural genes fliC and fljB in ΔDsrA, which have been implicated as major proinflammatory determinants. This study serves to highlight the role of sRNAs such as DsrA in both acid tolerance and virulence of S. Typhimurium. Additionally the robust phenotype of non-invasiveness could be exploited in developing SPI-I attenuated S. Typhimurium strains without disrupting SPI-I genes.